Pengembangan Sistem Manajemen Asset Pada PT. Pelindo IV Cabang Balikpapan Berbasis Android - Riswandi Meifi Mardani; Wildan Suharso; Ilyas Nuryasin (Universitas Muhammadiyah Malang, 2023)
Inventory is an activity or act of physically counting and classifying goods, and assessing their suitability for the purpose based on the condition of an item. In addition, this activity records incoming or outgoing goods, then records the history of the existence of the goods before and after being sent, who is responsible for taking or moving them and how the state of the Prototype Process used in this study with reference to the system design process to be developed can be defined. as a working model or working model of software fundamentals or developing software for the purpose of testing product concepts or workflows. The product is in accordance with what was stated by Roger S. Pressman. Prototyping is an iterative process of system development in which the results of observable requirements are transformed into a working system that is continuously improved through collaboration between users and analysts. Based on the performance results of developing an asset management information system, it shows that the prototype method has been successfully implemented as evidenced by the results of two application tests, namely black box testing and UAT testing. Updating new data streams with more systematic and informed goals, it is expected that all asset data are recorded accurately, data processing is fast and centrally managed, data management is more efficient and effective, and reporting systems can be implemented at any time if needed.